The association of serum vascular endothelial growth factor levels and psoriasis vulgaris: A protocol for systematic review and meta-analysis - Gong, Juan (Medicine (Baltimore), 2020)
BACKGROUND: In recent years, more and more attention has been paid to the role of skin microcirculation in the pathogenesis of psoriasis. The vascular network of the skin is mainly distributed in the dermis and the subcutaneous fat layer join. The microvessels are composed of terminal arterioles, arteriovenous capillaries, and postcapillary venules. Vascular endothelial growth factor (VEGF) plays an important role in the pathogenesis of psoriasis by promoting angiogenesis. The purpose of this study is to evaluate the relationship between serum VEGF and psoriasis vulgaris. METHODS: Embase, CENTRAL, PubMed, China Biology Medicine Database, China National Knowledge Database, Wan Fang Database, and Chong Qing VIP Database will be searched to collect case-control studies and cohort studies and evaluate the relationship between serum VEGF and psoriasis vulgaris. The search time limits will be from the establishment of the database to December 2020. Two researchers will independently screen the studies, extract data, and evaluate the risk of bias of the studies. The Meta-analysis will be carried out with the RevMan5.3 software. The quality of all included studies will be evaluated by the Newcastle-Ottawa scale. RESULTS: This study will evaluate the relationship between serum VEGF and the pathogenesis of psoriasis vulgaris. CONCLUSION: This study will provide a theoretical basis for the pathogenesis of psoriasis vulgaris. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/6DV8P